Strategi Guru PAI dalam Meningkatkan Motivasi Siswa Membaca Al-Qur’an di SMAN 2 Sungai Limau - Kartini, Fina; Ilmi, Darul; Aprison, Wedra; Charles, Charles (STAI Denpasar Bali, 2024)
Islamic education plays an important role in developing learners holistically, including in increasing their motivation in reading the Qur'an. This article highlights the strategies of Islamic Education teachers at SMAN 2 Sungai Limau in improving students' motivation to read the Qur'an. In the context of qualitative research, the strategies implemented by teachers include giving rewards, repetition, wise punishment, awakening students' desire, and intensive guidance. The results show that these strategies are effective in increasing students' interest and enthusiasm in reading the Qur'an, although there are still some inhibiting factors such as lack of motivation from general subject teachers and the influence of the family environment. However, cooperation between teachers, parents, and the environment is expected to significantly strengthen students' motivation in reading the Qur'an.